Impact of Interest Rates on Leveraged Buyout Capital Structure : Analysis of Interest Rates Relationship to Leveraged Buyouts - Melkoniemi, Toni Samuli (My University, 2025)
This thesis explores the relationship between interest rates and leveraged buyouts. The main objective is to understand the determinants behind capital structure decisions made in LBOs. Most common capital structure theories used to analyze corporate capital structures fail to explain the decisions made in private equity LBOs. Previous literature seems to mostly agree on the fact that LBO activity and capital structure is determined by the availability of debt. The thesis focuses on analyzing the possible effects of interest rates on debt availability for PE funds. LBOs heavily rely on high-yield bond market for financing, as debt is raised as extensively as possible. The thesis finds that interest rates are only part of the factors determining LBO capital structure. Credit market conditions seem to be the main determinant for successful deal financing, as PE funds are reported to benefit from mispricing of equity, debt and loose credit conditions. Literature reports a negative relationship between credit spreads and nominal interest rates against LBO activity and leverage ratio. Successful LBOs need precise credit market timing and market timing in general. Tämä tutkielma tarkastelee korkotason ja velkarahoitteisten yritysostojen välistä suhdetta. Päätavoitteena on ymmärtää pääomarakenteeseen liittyviä päätöksiä, joita velkarahoitteisissa yritysostoissa tehdään. Yleisimmät rahoitusteoriat, joita käytetään yritysten pääomarakenteiden analysointiin, eivät kykene selittämään pääomasijoittajien tekemiä päätöksiä velkarahoitteisissa yritysostoissa. Aiempi kirjallisuus on pääosin yksimielinen siitä, että velkarahoitteisten yritysostojen määrä niiden ja pääomarakenne määräytyvät velkarahoituksen saatavuuden perusteella. Tutkielma keskittyy analysoimaan mahdollisia korkotason vaikutuksia pääomarahastojen velkarahoituksen saatavuuteen. Velkarahoitteiset yritysostot tukeutuvat vahvasti korkeakorkoisiin joukkovelkakirjoihin, sillä velkaa pyritään hankkimaan mahdollisimman paljon. Tutkielman tulokset osoittavat, että korkotaso on vain yksi velkarahoitteisen yritysoston pääomarakennetta määrittävistä tekijöistä. Keskeisin tekijä onnistuneen velkarahoituksen kannalta näyttää olevan luottomarkkinoiden tila, sillä pääomarahastot hyötyvät osakkeiden ja velan hinnoitteluvirheistä sekä löysistä luottoehdoista. Aiemmat tutkimukset havaitsevat, että luottomarginaaleilla ja nimelliskoroilla on negatiivinen suhde velkarahoitteisten yritysostojen määrään ja velkavivun suuruuteen nähden. Onnistuneet velkarahoitteiset yritysostot vaativat tarkkaa ajoitusta sekä luottomarkkinoilla että markkinoilla yleisesti.
Keywords: pääomasijoittaminen; korko; yrityskaupat; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Kauppatieteiden kandidaattiohjelma|en=Bachelor Programme in Business Studies|; Rahoitus